The Linguistic Landscape of Religious Tourism Destination in Bangkalan, Madura: Functions and Identity Representation - Rosyida Ekawati; Desi Puspitasari; Diah Ikawati Ayuningtias (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
Languages in public spaces are one of the linguistic phenomena in society. This study examines the form of written language in public spaces in a particular religious tourism destination, namely Syaikhona Cholil mosque and Cemetery complex, in Bangkalan Regency, Madura, in terms of linguistic landscape (LL). This study examines the functions of each sign and its identity representation. The data are photographic evidence of language use in this area. There are several steps to collect data by identifying the LL, photographing LL to capture language issues in public spaces, classifying data based on their taxonomies, and classifying the use of language patterns, functions, and representations of identity. LL in this religious tourism destination is monolingual LL in which it only used Indonesian language, without using other languages, either ethnic language or foreign language. The functions of the LL are signs of information, signs of warning, appeal and prohibition, road signs, and building signs. The use of LL shows the identity as the unity Indonesian and the ownership or regulator of the destination. Although the place is in Madura, but there is no Madurese language used, Indonesian is the identity of the nation, which must be maintained and preserved. The use of LL in the area also shows the owner or the management team of the object that has the right to regulate its use.